Bio-equivalent doses of recombinant HCG and recombinant LH during ovarian stimulation result in similar oestradiol output: a randomized controlled study. Issue 2 (August 2017) - Alsbjerg, Birgit; Elbaek, Helle Olesen; Laursen, Rita Jakubcionyte; Povlsen, Betina Boel; Haahr, Thor; Yding Andersen, Claus; Humaidan, Peter
Abstract: In nature, HCG is secreted by the implanting embryo from peri-implantation and onwards. In contrast, LH is mandatory for steroidogenesis and follicular development during the follicular phase, working in synergy with FSH. Moreover, LH is mandatory for the function of the corpus luteum. Although LH and HCG bind to the same receptor, significant molecular, structural and functional differences exist, inducing differences in bioactivity. This randomized controlled study compared the effect of recombinant FSH stimulation combined with daily either micro-dose recombinant HCG or recombinant LH supplementation in a 1:1 bioactivity ratio from day 1 of stimulation in a long gonadotrophin releasing hormone agonist down regulation protocol. A total of 100 patients from a public clinic completed the study. The primary end-point was the oestradiol level on the day of ovulation trigger and the median oestradiol level in the HCG supplemented group was 8662 pmol/l versus 9203 pmol/l in the recombinant LH supplemented group; therefore, no significant difference was found. Moreover, no differences were observed in the number of oocytes retrieved or in the live birth rate. We conclude that recombinant HCG and recombinant LH are equally effective in boosting oestradiol synthesis during ovarian stimulation when used in a 1:1 bioactivity ratio.